Meg Robinson: capstone - Robinson, Meg, artist (Colorado State University. Libraries, 2023)
The artist's statement: I'm a graphic designer, illustrator, and communicator. My body of work represents sparks of connection within people and places that feel child-like or romantic, but guaranteed are always 100% genuine. Skills such as being adaptive, observant, and curious bolster me, but being continually open to learn allows me to thrive. In the professional experience I've gathered thus far the most fun I have is always in the process. I love watching a question getted picked and prodded at. I investigate using a variety of materials, but have found a home in graphic design, brand identity, and community engagement. Fiber Art continues to capture my heart from time to time and helps me remember to never fear a new material or method. If anything, I'll always be curiously investigating a new infatuation. My background in graphic design, art history, and journalism becomes intertwined in my career often because of the valuable skills gained in those fields. Those skills include creative problem solving, honed research methods, navigating design systems, and concise language. Aside from excelling in these areas, I have a true passion for the ways in which design, history, and communication coincide.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design